2020
DOI: 10.1111/eulj.12405
|View full text |Cite
|
Sign up to set email alerts
|

The future of EU Foreign, Security and Defence Policy: Assessing legal options for improvement

Abstract: The EU's Common Foreign, Security and Defence Policy found its way into the Treaty 30 years ago, but it is still confronted with 'specific rules and procedures' that seem to stand in the way of its effectiveness. Against the background of the Conference on the Future of Europe, this contribution aims to identify ways to improve the CFSP's functionality, on the basis of both existing scholarly work and an empirical assessment of the last 10 years of the Union's foreign policy. By focusing on legal rather than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Interestingly, this is followed by so-called implementing decisions based on Article 31(2) TEU (29.8%), which are mostly used to amend existing sanctions. Based on these results, the authors conclude that "sanctions are by far the most used instruments in the Unions foreign policy" (Wessel et al 2022; see also Wouters 2017, 78-80).…”
Section: Strategic Autonony In Security and Defencementioning
confidence: 95%
“…Interestingly, this is followed by so-called implementing decisions based on Article 31(2) TEU (29.8%), which are mostly used to amend existing sanctions. Based on these results, the authors conclude that "sanctions are by far the most used instruments in the Unions foreign policy" (Wessel et al 2022; see also Wouters 2017, 78-80).…”
Section: Strategic Autonony In Security and Defencementioning
confidence: 95%
“…Paul James Cardwell has convincingly argued that "the extent to which sanctions have been imposed [in the EU], or at the very least discussed in the Council, means that it is little exaggeration to say that the CFSP has become oriented towards sanctions as an appropriate response to global or regional problems" (Cardwell, 2015: 288). Similarly, Ramses Wessel and others have found that approximately 80% of CFSP decisions are either about establishing or amending sanctions regimes based on Articles 29 and 31(2) of the Treaty on European Union (TEU) respectively (Wessel et al, 2021).…”
Section: In Love With Sanctions: Eu and Us Approaches To Sanctionsmentioning
confidence: 98%
“…111 Even the stronger of the three clauses, namely Article 42(7) of the TEU, reflects the competing "demands of groups" of EU member States "wanting to retain a stance on neutrality, those wanting to retain the focus of defence policy in NATO and those with ambitions for a 'European' defence force". 112 This raises questions about the level of commitment and therefore deterrent effect of the EU's defence and solidarity clauses, "in particular at a time when political fault lines within the Union itself are so deep and numerous". 113 Furthermore, the place of the nuclear deterrent in the ESA and the defence of Europe is ambiguous: "[while] this issue has traditionally been viewed as falling within the exclusive remit of NATO, the uncertainties about the US commitment has now sparked debates in foreign policy circles about whether and how Europeans should and could find a substitute to America's ultimate guarantee", in particular the extension of the French nuclear deterrent to member States of the EU.…”
Section: The Eu's Ambiguous Role: Enforcing the Rule Of Law By Non-fo...mentioning
confidence: 99%
“…As Wessel and others conclude, sovereignty and the "Member States' general unwillingness to pool parts of it to allow the Union to more easily formulate its foreign and security policy" must be considered "as the greatest impediment to an 'ever closer union' in terms of foreign and security policy". 119…”
Section: The Eu's Ambiguous Role: Enforcing the Rule Of Law By Non-fo...mentioning
confidence: 99%